Nutritional composition of rice field eel, Monopterus albus (Zuiew, 1793) as a potential food source - Muslimatun binti Arizal
Rice field eel (Monopterus a/bus) is a freshwater fish that can be found extensively in paddy field area in Malaysia. Although, Monopterus a/bus is considered as a highly nutritious food, however, locals are not favour Monopterus a/bus as a daily cuisine because of their undesireble physical appearance and it is only hyped and used as a folk remedy for medicinal purposes. There is also lack of nutritional information of this species in Malaysia due to minimal or limited study. The data from this study could be used as a baseline data of nutritive value of Monopterus a/bus in Malaysia to promote the consumption of this species not only for medicinal purposes but also as daily consumption. The objectives of this study include determining the nutritive values such as proximate, minerals and fatty acids composition of Monopterus albus, evaluating the nutritional composition of Monopterus a/bus from different locality and sizes and to study the correlation of nutritional composition of Monopterus albus. Monopterus albus samples were categorized into two market avaibility size category; treatment 1 (Size I) with average body weight of 134.33 ± 3.63 g and average total length of 53.88 ± 0.45 ern; treatment 2 (Size 2) with average body weight of 3l.16 ± 1.19 g and average total length of35.21 ± 0.35 cm and were sampled from three states in Peninsular Malaysia (Selangor, Perak and Terengganu). Samples were analyzed for proximate composition, percentage of moisture, ash, crude protein and crude lipid. Minerals composition was determined by inductively coupled plasma - optical emission spectrometry (lCP-OES) while fatty acids composition was determined by gas chromatography - mass spectrometry (GCMS). Two-way ANOVA was applied to examine the relationship between size and compositions. All data analysis was carried out using IBM SPSS Statistic 22 and reported in mean ± standard error. Significance level was determined at values < 0.05 and 0.001. The most abundant macroelernei was Calcium with concentration afZ5<O'82'. Ingt~- 0468.50 mg/kg while Zinc vas the dominant microelement found in Monopterus a/bus witli COl mtrarion ofJ, .95 mg/kg - 49.95 mg/kg. Results show that the highest fatty acids found in Monopterus albus were palmitic acid (C16:0) and stearic acid (C18:0). Besides that, Perak Size 2 eel shows the highest concentration of Q-3 and Q-6 fatty acids, with value of 6.84 ± 1.16% and 13.86 ± 0.27% respectively. The study found that Monopterus a/bus was high in protein content (49.67% to 76.51%) and low in lipid (2.26% to 2.66%), suggesting the suitability of this fish species to be consumed by human. Monopterus albus has potential minerals and fatty acids required in human's daily diet and may be considered as a potential fish with high nutritive value in Malaysia's aquaculture.